2022
DOI: 10.3390/polym14061074
|View full text |Cite
|
Sign up to set email alerts
|

Application of Soft Computing Techniques to Predict the Strength of Geopolymer Composites

Abstract: Geopolymers may be the best alternative to ordinary Portland cement because they are manufactured using waste materials enriched in aluminosilicate. Research on geopolymer composites is accelerating. However, considerable work, expense, and time are needed to cast, cure, and test specimens. The application of computational methods to the stated objective is critical for speedy and cost-effective research. In this study, supervised machine learning approaches were employed to predict the compressive strength of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…It was noted that 61% of the error data was below 0.5 MPa, 30% was from 0.5 to 1 MPa, and only 8% was higher than 1 MPa. Previous studies also reported the better performance of the random forest model in forecasting the various properties of different materials in terms of superior R 2 and lower error values [47,52,53]. This analysis revealed a higher accuracy of the random forest model with respect to the AdaBoost models.…”
Section: Random Forest Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…It was noted that 61% of the error data was below 0.5 MPa, 30% was from 0.5 to 1 MPa, and only 8% was higher than 1 MPa. Previous studies also reported the better performance of the random forest model in forecasting the various properties of different materials in terms of superior R 2 and lower error values [47,52,53]. This analysis revealed a higher accuracy of the random forest model with respect to the AdaBoost models.…”
Section: Random Forest Resultssupporting
confidence: 55%
“…It was noted that 60% of the error data was below 0.5 MPa, 27% ranged from 0.5 to 1 MPa, and only 13% was higher than 1 MPa. Wang, et al [47] reported that the AdaBoost machine learning approaches predicted the better compressive strength of geopolymer composites. Zhu, et al [54] used the machine learning to forecast the splitting-tensile strength (STS) of the concrete containing recycled aggregate (RA) and revealed that the precision level of the bagging model was better.…”
Section: Bagging Resultsmentioning
confidence: 99%
“…The error and R 2 values for the compressive strength of UHSC for XGBoost are more accurate than the bagging model. Wang, et al [ 33 ] reported that the AdaBoost machine learning approaches predicted the best compressive strength of geopolymer composites. Zhu, et al [ 40 ] used machine learning to forecast the splitting tensile strength (STS) of concrete containing recycled aggregate (RA) and revealed that the precision level of the bagging model was better.…”
Section: Resultsmentioning
confidence: 99%
“…Nine groups will be utilized for training the models and one will be used for validation. The lower error values (MAE and RMSE) and the higher R 2 values suggest the higher precision of a model [ 69 ]. Moreover, the process must be repeated 10 times to obtain a suitable decision.…”
Section: Model’s Validationmentioning
confidence: 99%